Design and fabrication of a quasi-ordered nanoporous silicon membrane suitable for thermally induced drug release - Chau C.F.; Melvin T. (2023)
The design and fabrication of an ordered nanoporous silicon membrane and integrated heater and temperature sensor is described. The methodology for fabrication of the nanoporous structure has been developed for integration within microelectromechanical systems. The structure is fabricated from a 500?m thick silicon ?100? wafer, which has been etched to provide 44mm 2membranes of 50?m thick. Quasi-ordered nanoporous silicon is created within the membrane, the nanopores are of uniform diameter (typical structures of the order of 105 5nm) and smooth sidewalls to a depth of ?300nm, in a hexagonal close-packed pattern of 200nm nearest neighbour. The porosity of typical fabricated samples is 31.5%. On the back side of the membrane, a heater and a temperature sensor are incorporated. Three different heater/temperature sensor designs were considered theoretically and the best design was then fabricated and studied experimentally. The results obtained provide both highly ordered nanoporous silicon fabrication methodology as well as evidence that the porous membrane can be heated without deleterious effect. 2012 IOP Publishing Ltd.